The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1981
DOI: 10.1007/bf03007805
|View full text |Cite
|
Sign up to set email alerts
|

A simple formula for adjusting arterial carbon dioxide tension

Abstract: To improve the accuracy of acid-base adjustment in mechanically ventilated patients we derived the formula: known arterial Pcoz x known minute ventilation Required minute ventilationdesired arterial Pco2 which allows calculation of the minute ventilation required to produce a desired arterial Pco2 by measuring the patient's existing arterial Pco2 and minute ventilation. This was tested in fifty patients using four types of ventilators and found to be statistically accurate, with a mean difference between predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 4 publications
(1 reference statement)
0
49
0
1
Order By: Relevance
“…Although this variation in dead space between Vt 6 and Vt 4 limits the possibility of comparing PaCO 2 and pH with both Vts, the purpose of this part of the study was just to determine if severe hypercapnia and respiratory acidosis could be avoided during ventilation with Vt 4. Although 30 minutes may seem a short period, it has been shown that it is enough to reach a new equilibrium in PaCO 2 after changes in ventilation [25,26]. Our data suggest that a ventilatory strategy based on a Vt of 4 ml/kg would be feasible in several ARDS patients.…”
Section: Discussionmentioning
confidence: 65%
“…Although this variation in dead space between Vt 6 and Vt 4 limits the possibility of comparing PaCO 2 and pH with both Vts, the purpose of this part of the study was just to determine if severe hypercapnia and respiratory acidosis could be avoided during ventilation with Vt 4. Although 30 minutes may seem a short period, it has been shown that it is enough to reach a new equilibrium in PaCO 2 after changes in ventilation [25,26]. Our data suggest that a ventilatory strategy based on a Vt of 4 ml/kg would be feasible in several ARDS patients.…”
Section: Discussionmentioning
confidence: 65%
“…A correlation between high dead space and mortality has been found in patients with ARDS [26]. Therefore, in our analysis, we used the “corrected minute ventilation” (VE corr ) as a surrogate for dead space [27] and found that even after adjusting for VE corr , severe hypercapnia remains strongly associated with mortality. Moreover, Brown et al [32] showed that a minute ventilation of >13.9 l/min was an important predictor of hospital mortality at 90 days in acute lung injury, similar to our findings (>14 l/min).…”
Section: Discussionmentioning
confidence: 99%
“…Because clinical practices regarding MV strategies in patients diagnosed with ARDS have changed over time, the model was also adjusted for the period of the study. In addition, because dead space is strongly associated with mortality [26] and may be a confounding factor for hypercapnia, we calculated the corrected minute ventilation (VE corr ) for a normal PaCO 2 (calculated as minute ventilation × actual PaCO 2 /40 mmHg) as a surrogate for dead space [27] and introduced this as a co-variable into the univariate and multivariate model. We created a vertical plot showing the adjusted odds ratio (OR) for ICU mortality and PaCO 2 as categorized.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the ARDS Definition Task Force 9 attempted to use corrected minute ventilation (i.e. [Pa CO2 x minute ventilation] / 40) 21 as a potential surrogate for dead-space in defining those with severe lung injury. Yet this surrogate was not used in the final definition because of a “lack of evidence for predictive validity”.…”
Section: Discussionmentioning
confidence: 99%